How Do Pharmacists Distribute Their Work Time during a Clinical Intervention Trial?-A Time and Motion Study - Renata Vesela Holis; Renate Elenjord; Elin Christina Lehnbom; Sigrid Andersen; Marie Fagerli; Tine Johnsgård; Birgitte Zahl-Holmstad; Kristian Svendsen; Marit Waaseth; Frode Skjold; Beate Hennie Garcia (MDPI AG, 2024)
Emergency departments (EDs) handle urgent medical needs for a diverse population. Medication errors and adverse drug events pose safety risks in the ED. Clinical pharmacists, experts in medication use, play a crucial role in identifying and optimizing medication therapy. The aim of this study was to investigate how clinical pharmacists introduced into the ED interdisciplinary teams distribute their work time. In a time and motion study, we used the Work Observation Method By Activity Timing (WOMBAT) to observe pharmacists in two Norwegian EDs. The pragmatic approach allowed pharmacists to adapt to ED personnel and patient needs. The pharmacists spent 41.8% of their work time on medication-related tasks, especially those linked to medication reconciliation, including documenting medication-related issues (16.2%), reading and retrieving written information (9.6%), and obtaining oral information about medication use from patients (9.5%). The remaining time was spent on non-medication-related tasks (41.8%), and on standby and movement (17.4%). In conclusion, ED pharmacists spent 42% of their work time on medication-related tasks, predominantly medication reconciliation. Their relatively new role in the interdisciplinary team may have limited their broader clinical impact. Relative to other ED healthcare professionals, ED pharmacists' goal remains to ensure accurate patient medication lists and appropriate medication use.